PENCEMARAN NAMA BAIK DALAM PRESPEKTIVE KONSTITUSI DAN UU ITE - Kusumastuti, Dora - (Widya Wacana: Jurnal Ilmiah, 2012)
Abstract: The utilization of information and communication technology on the one hand to contribute tothe increased well-being and human civilization. On the other hand the advancement of electronicinformation technology can be used to perform actions that are against the law, the law to harm people,society and the State. The trend continued development of technology certainly brings a lot ofimplications that must be anticipated and should also be wary of. That effort has now spawned a legalproduct in the form of Law Number 11 Year 2008 on Information and Electronic Transactions (ITE). In thedevelopment of the Act ITE particularly in article 27 concerning defamation lawsuit has been amendedseveral times in Makamah Constitution. Some claim assumes that in article 27, paragraph 3 is consideredunconstitutional, because it has the freedom of expression, and has the interpretation is too general. Thisstudy aimed to determine whether Article 27 of the Act is unconstitutional ITE.Key Words: Defamation, Electronic transaction Information Laws